Imaging and Radioanalytical Techniques in Interdisciplinary Research (IntechOpen, 2013)
The overall goal of this book is to promote research and development of imaging and radioanalytical techniques by publishing high-quality chapters in this rapidly growing interdisciplinary field. This book discusses the principles and applications of imaging and radioanalytical techniques across a wide spectrum of interdisciplinary science, technology and medicine, where these techniques are expected to make significant difference and contribution. It also explores the history of the field, current trends, and future directions. The book focuses mainly on cutting-edge applications, and associated equipments and methods, such as instrumentation systems and computing hardware/software. The primary target audience for this book includes students, researchers, clinicians, and professionals who are interested in medical and ground penetrating radar (GPR) imaging, and radioanalytical techniques.